How green credit policy shapes financial performance: Evidence from Chinese listed construction energy-saving enterprise - Li, Xiaoqiu; Lu, Yiling (Frontiers in Environmental Science, 2022)
This study uses the introduction of the Green Credit Guidelines in 2012 as a quasi-natural experiment. We selected Chinese A-share listed enterprises from 2004 to 2020 as the sample and applied PSM-DID to examine the impact of the green credit policy on the performance of building energy-saving enterprises. The study revealed that: (1) green credit policies have a significant contribution to the performance of building energy-saving enterprises. In addition, it still holds after the robustness tests (replacing the PSM matching method and adding or subtracting the two methods of control variables) and the placebo test. (2) A positive correlation between the performance of building energy-saving enterprises and short-term debt. Meanwhile, short-term debt is a mediating variable between green credit policies and the performance of building energy-saving enterprises. (3) The impact of green credit policies on the performance of non-state-owned (non-SOEs) was more pronounced compared to state-owned (SOEs). This study reveals the micro effects of green credit policy from the perspective of the performance of building energy-saving enterprises. It not only helps to understand the economic effects of green credit policy, but also provides corresponding insights for the subsequent promotion of green credit policy and building energy-saving enterprise development systems.